Heterologous expression of Xylanase gene from klebsiella pneumoniae in E.coli BL21 (DE3) - Suhaila, Bt Zainol (Universiti Malaysia Sarawak (UNIMAS), 2012)
A xylanase DNA sequence with a total length of 642 bp was isolated from a xylanolytic Klebsiella pneumoniae bacterium in order to attempt heterologous expression in E. coli BL21 (DE3). A xylanase gene primer was designed with the addition of BamHI and EcoRI restriction enzyme sites in order get a full xylanase gene that is in-frame with pST AG expression vector. The isolated xylanase was amplified using the designed xylanase primer through PCR, then cloned and expressed in E. coli BUI (DE3). In-silico characterization showed that the recombinant xylanase without S-tag has a molecular weight of 23.9 kDa and a pI of 9.32. The signal peptide cleavage site for the recombinant xylanase and its native xylanase was predicted to be between residues 61 and 62, and residues 28 and 29 respectively. The activity of crude recombinant xylanase from freeze and thaw method and sonication method is 2.015 UlmL and 0.904 U/mL respectively, which is higher than the crude native xylanase activity showing only 0.642 UlmL at maximum. Staining of the birchwood xylan agar plate with Congo red showed clearing zone around E. coli BL21 (DE3) that has positive recombinant xylanase even without the addition of IPTG, implying leaky expression had occur, and that E. coli BL21 (DE3) secretion system had recognizes the signal sequence of the native xylanase and proceeds to cleave it, then secreting out the mature protein into culture medium.